Building a Sustainable Learning Ecosystem: The School's Role in Promoting Environmental Awareness among Students - Sudrajat, Didi; Wahyuni, Sri; Saputri, Dwi Yuniasih; Prayitno, Hadi (PT. Anagata Sembagi Education, 2025)
Growing environmental degradation has become a pressing global issue, highlighting the importance of education in shaping the environmental awareness of the younger generation. This study aims to fill the gap in the literature regarding the contribution of schools in building sustainable learning ecosystems that promote environmental awareness among students. This study uses a qualitative method with a case study approach in several schools that implement environmental education programs. Data were obtained through in-depth interviews with principals, teachers, and students, observation of school activities, and document analysis of environment-related education policies. The results showed that the integration of environmental issues in the curriculum, the implementation of nature-based extracurricular programs, and the management of environmentally friendly school facilities play a significant role in building students' awareness of sustainability. Activities such as reforestation, waste management and environmental campaigns allow students to be directly involved in sustainability practices, which in turn increases their understanding of and responsibility for environmental conservation. The involvement of various stakeholders, including families and communities, to support the creation of an effective learning ecosystem. This research provides strategic recommendations for policy makers to design a more integrated and impactful environmental education program. This research is expected to serve as a guide in efforts to strengthen environmental awareness through an educational approach